Agent-based modelling: A methodology for the analysis of qualitative development processes - Andreas Pyka; Thomas Grebel (Universität Augsburg, Institut für Volkswirtschaftslehre, 2003)
The tremendous development of an easy access to computational power within the last 30 years has led to the widespread use of numerical approaches in almost all scientific disciplines. The first generation of simulation models was rather focused on stylized empirical phenomena. With agent-based modelling, however, the trade-off between simplicity in modelling and taking into account the complexity of the socio-economic reality has been enhanced to a large extent. This paper serves as a basic instruction on how to model qualitative change using an agent-based modelling procedure. The necessity to focus on qualitative change is discussed, agent-based modelling is explained and finally an example is given to show the basic simplicity in modelling.
urn:nbn:de:bvb:384-opus4-712064
Keywords: O30; B52; 330; agent-based modelling; methodology; evolutionary economics; qualitative change; Agent-based Model; Evolutionsökonomik; Simulation; Theorie